Origin of slow-rotating minor bodies by tidal decoupling of binary pairs. Issue 4 (23rd November 2016) - Brunini, A.
Abstract: In this paper, we show that the decoupling of binary pairs by tidal interaction and Kozai oscillations acting together can generate single objects in a slow-rotation-rate state. This mechanism has the merit of not being strongly dependent on the size or shape of the objects. The key parameter leading the process is ω/ n, the ratio between the rotation rate and the orbital mean motion of the binary, which must be >1. The proposed mechanism could also operate in other populations of minor bodies.